Kinetics of Oxidation of Indole in High Indole Concentration Range by Bromamine-B in Alkaline Medium Catalysed by Os(VIII) - Demappa, T.; Ananda, S. (Asian Journal of Chemistry, 2010)
The kinetics of oxidation of indole (In) in bigh indole concentration range by sodium N-bromobenzene sulphonamide (BAB) in alkaline medium in presence of OSO4 catalyst have been investigated at 30°C. The reaction rate shows a first order dependence of rate on [BAB]o and [Indole], and inverse first order dependence of rate on [OH- ] and first order on [OSO4]. Addition of halide ions and variation of ionic strength and dielectric constant of the medium do not have any sigtlflcant effect on the reaction rate. Thermodynamic parameters have been evaluated.